2008
DOI: 10.1042/bj20081335
|View full text |Cite
|
Sign up to set email alerts
|

When expressed in yeast, mammalian mitogen-activated protein kinases lose proper regulation and become spontaneously phosphorylated

Abstract: MAPKs (mitogen-activated protein kinases) are key components in cell signalling pathways. Under optimal growth conditions, their activity is kept off, but in response to stimulation it is dramatically evoked. Because of the high degree of evolutionary conservation at the levels of sequence and mode of activation, MAPKs are believed to share similar regulatory mechanisms in all eukaryotes and to be functionally substitutable between them. To assess the reliability of this notion, we systematically analysed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 44 publications
(58 reference statements)
1
33
0
Order By: Relevance
“…[23][24][25] Plants share the MAPKKK-MAPKK-MAPK cascade with, however, the dual phosphorylation sequence of the activation loop limited to TEY or TDY. 26 While recent results identify mechanisms specific to yeast, 12,23 conservation among vertebrates (especially the superclass of jawed vertebrates Gnathostomata) is much higher, sharing the differentiation into four major subgroups. 27 Three p38 MAPKs from Salmo salar (Atlantic salmon) have been identified so far, with ubiquitous tissue distribution, including expression in immune organs such as spleen and head kidney.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[23][24][25] Plants share the MAPKKK-MAPKK-MAPK cascade with, however, the dual phosphorylation sequence of the activation loop limited to TEY or TDY. 26 While recent results identify mechanisms specific to yeast, 12,23 conservation among vertebrates (especially the superclass of jawed vertebrates Gnathostomata) is much higher, sharing the differentiation into four major subgroups. 27 Three p38 MAPKs from Salmo salar (Atlantic salmon) have been identified so far, with ubiquitous tissue distribution, including expression in immune organs such as spleen and head kidney.…”
Section: Introductionmentioning
confidence: 98%
“…Activation of p38α via autophosphorylation is likely the key mechanism for T-cell antigen receptor signaling 9,10 and is also implicated in myocardial ischemic damage. 11,12 Studies have shown that mutations and phosphorylation 13,14 can enhance or initiate the noncanonical autophosphorylation pathway; however, structures and regulatory mechanisms of the dimeric state responsible for autophosphorylation are unknown. The autocatalytic noncanonical pathway leads to single phosphorylation of the threonine of the TxY activation loop sequence, in contrast to the dual phosphorylation of MKK activation.…”
Section: Introductionmentioning
confidence: 99%
“…Ser409 in the tau protein was specifically identified as a key residue, whose phosphorylation is crucial to produce the aggregated forms in yeast [77]. Thus, although aggregates of hyperphosphorylated tau do form [78] could be used for studies of effects on tau phosphorylation and aggregation upon co-expression PP2A function in double mutant pph21Δ pph22Δ upon co-expression with tau PIN1 function in ess1Δ upon co-expression with tau [61,79] Use of deletions to study specific modifications of tau use of rim11Δ/mds1Δ to reduce tau phosphorylation and study its aggregation [76] sod2Δ to study oxidative stress [77] and its effect on tau aggregation temperature-sensitive mutants in proteasomal proteases to investigate their effect on tau processing Heterologous gene expression tau for purposes of protein production and biochemical/immunological approaches [77,81] expression of tau and annexin A2 for Co-IPs [66] expression of all three heterologous genes encoding human AMPK subunits [81] to study their effect on tau phosphorylation and aggregation expression of genes for modifying enzymes (e.g. acetyltransferase p300 [55] to study the role of these modifications for tau aggregation Chimeric gene expression expression of tau and human tubulin or a hybrid yeast/human tubulin gene to investigate the interaction with microtubules in yeast Yeast two-hybrid assays (YTH) identification of E3 ubiquitin ligase modifying tau [54] and other new interactors Protein aggregation assays application of colony-colour assay for prion functions to tau aggregation [80] use of fluorescence labels either in conjunction with FACS as demonstrated for Aß [83] or with FRET to study tau aggregation and its interaction with other proteins Synthetic lethal screens use of a platform yeast strain co-expressing the genes for tau and the Aß peptide to screen for suppressors from cDNA libraries or for high-throughput drug screens use of tau overexpression strain to screen for cDNA clones enhancing/provoking toxicity [4] Chronological aging test the effects of tau variants on long-term survival of yeast transformants in synthetic medium [9] to obtain a phenotype useful for genetic screens of the tau interactome [9] Synthetic biology establish entire human modification or signaling pathways in yeast platform strains (lacking the yeast orthologous genes if required and complemented by the human counterparts) to establish a "humanized yeast physiology" * aspects also applicable to the alternative non-conventional yeast K. lactis (but not yet examined for tau-related functions) are underlined.…”
Section: Tau Expression In Saccharomyces Cerevisiae and Merits Of Klumentioning
confidence: 99%
“…Although the exact role of ERK1/2 phosphorylation in tau-induced neuronal cell death under physiological conditions is still disputed [99], the yeast system may help to resolve some of the problems. In fact, hyperactive forms of both MAPK isoforms have been expressed in yeast [100], and wild-type forms were shown to be constitutively phosphorylated by a number of yeast MAPKKs [78]. Together with episomal expression of tau, all the tools are thus available to investigate the effects that ERK1/2 variants have on the phosphorylation and aggregation capacity of tau.…”
Section: Genetic Screens In Yeast -The Past the Present And The Futurementioning
confidence: 99%
“…We took advantage of the yeast MPK1 pathway, the MAPK of which, Mpk1, belongs to the ERK family of kinases (1,22). Furthermore, the human Erk2 can functionally replace Mpk1 (68). The Mpk1 cascade is responsible for the integrity of the cell wall of the yeast (58 -60).…”
Section: Mutations That Render Hog1 and P38 Intrinsically Activementioning
confidence: 99%